2008
DOI: 10.1634/stemcells.2008-0325
|View full text |Cite
|
Sign up to set email alerts
|

A Reservoir of Brown Adipocyte Progenitors in Human Skeletal Muscle

Abstract: Brown adipose tissue uncoupling protein-1 (UCP1) plays a major role in the control of energy balance in rodents. It has long been thought, however, that there is no physiologically relevant UCP1 expression in adult humans. In this study we show, using an original approach consisting of sorting cells from various tissues and differentiating them in an adipogenic medium, that a stationary population of skeletal muscle cells expressing the CD34 surface protein can differentiate in vitro into genuine brown adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 51 publications
3
111
0
4
Order By: Relevance
“…Myf5-expressing progenitors can give rise to both skeletal muscle and interscapular brown fat (13). In accordance with these observations, brown-fat progenitors have also been identified in human skeletal muscle (14). However, not all brown-fat cells are derived from myf5-expressing progenitors.…”
supporting
confidence: 65%
“…Myf5-expressing progenitors can give rise to both skeletal muscle and interscapular brown fat (13). In accordance with these observations, brown-fat progenitors have also been identified in human skeletal muscle (14). However, not all brown-fat cells are derived from myf5-expressing progenitors.…”
supporting
confidence: 65%
“…In addition, consistent with a common muscle and BAT progenitor, other groups have reported that (i) BAT and skeletal muscle are derived from a common progenitor in the dermomyotome (Atit et al, 2006), (ii) myogenin-deficient neonatal mice not only have impaired muscle development but also exhibit an accumulation of brown adipocytes in the anatomical location of muscles (Hasty et al, 1993) and (iii) brown but not white adipose precursors express many genes and microRNA specific to muscle precursors (Timmons et al, 2007). Finally, adult skeletal muscle has been shown to be a 'reservoir' of brown adipocyte progenitors in humans (Crisan et al, 2008) and mice (Almind et al, 2007). Whether a single Myf51 cell gives rise to both BATand muscle, or whether there are distinct populations of Myf51 progenitors remains unknown.…”
Section: Molecular Control Of the Cell Lineage Fatementioning
confidence: 99%
“…8 We also reported the existence of low levels of UCP1 mRNA in human muscle biopsies suggesting the presence of mature brown adipocytes in adult skeletal muscle. 8 As transgenic expression of UCP1 in muscle is known to increase insulin-mediated glucose uptake, 9 human skeletal muscle brown adipocytes might protect not only from obesity but also from insulin resistance.…”
Section: Introductionmentioning
confidence: 62%
“…8 Cyclophilin A was used as a control to account for any variations due to the efficiency of the reverse transcription. The upstream and downstream oligonucleotide primers were chosen on both sides of an intron to prevent amplification of contaminating genomic DNA.…”
Section: Reverse Transcription and Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation